Serological Relationship of the Tacaribe Complex of Viruses to Lymphocytic Choriomeningitis Virus - Rowe, Wallace P. (1970)
By means of the indirect fluorescent-antibody test, cross serological reactivity was demonstrated between lymphocytic choriomeningitis (LCM) virus and the viruses of the Tacaribe complex. Antisera to all members of the Tacaribe complex reacted with LCM virus; LCM antisera gave significant staining of Amapari virus, but minimal or inconsistent reactions with Tacaribe virus, and no reaction with two other viruses of the Tacaribe complex. A low level cross-reaction was observed in complement fixation tests of Machupo and Pichinde antisera against LCM antigen. Immunization with Tacaribe and Amapari viruses did not protect mice against challenge with LCM virus. Because of the identical appearance of the virions, the sharing of antigens, and the many biological similarities between LCM and the Tacaribe complex viruses, it is proposed that they be considered as constituting a new taxonomic group of viruses.